Cognitive Outcome of Acth-Treated Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The long-term cognitive and seizure outcomes of 37 patients with cryptogenic infantile spasms (onset, age 3 to 9 months) treated with high-dose synthetic adrenocorticotropic hormone (ACTH) (1 mg IM every 48 hrs for 2 weeks, 8-10-week slow taper, followed by oral prednisone, 10 mg/d for 1 month, and slow taper for 5 months or until age 1 year) were evaluated at Schneider Children's Medical Center of Israel, Petah Tiqva, Israel.